2017
DOI: 10.1016/j.healthpol.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluations of alcohol prevention interventions: Is the evidence sufficient? A review of methodological challenges

Abstract: HighlightsThere are few economic evaluations of alcohol prevention interventions.Consideration of impacts beyond an individual’s health in evaluations is limited.No published studies using other priority-setting methods in the alcohol area.Consideration of wider societal perspectives and health inequalities is minimal.Including inter-sectoral costs and consequences in evaluations is challenging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 56 publications
1
28
0
3
Order By: Relevance
“…The challenge with a CCA however is that it fails to offer any evidence on opportunity cost, hence the value of what is being displaced from choosing to invest resource in one particular way versus another. This limitation was also noted by Hill, 2017 in a recent review of economic evaluations of alcohol prevention interventions (Hill et al 2017).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The challenge with a CCA however is that it fails to offer any evidence on opportunity cost, hence the value of what is being displaced from choosing to invest resource in one particular way versus another. This limitation was also noted by Hill, 2017 in a recent review of economic evaluations of alcohol prevention interventions (Hill et al 2017).…”
Section: Discussionmentioning
confidence: 83%
“…In addition, there was a strong theme that the outcomes need to be broader than health with wellbeing revealed as a priority. This broader measure of outcome means that comparisons of cost-effectiveness can be made across different sectors and despite notable developments within health economics on the measurement of ‘capability wellbeing’ (Coast et al , 2008; Smith et al , 2012), recent reviews of economic evaluations of public health interventions report the majority to be cost-effectiveness analysis (White et al , 2018), conducted from a health care perspective (Hill et al , 2017). This is despite decision-making bodies such as NICE recommending greater use of a public sector or government perspective for public health economic evaluation (NICE, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are guidance documents available for conducting and reporting of public health economic evaluations (Edwards et al, 2013), there does seem to be a continued lack of availability of economic evidence for public health investment and for those that do exist, a heterogeneity in methods applied (Edwards et al, 2013;Hill, Vale, Hunter, Henderson, & Oluboyede, 2017;Lung et al, 2017). The U.K. NICE in 2014 updated its guidance for the evaluation of public health interventions recommending both a public sector and a societal approach that means that all relevant costs and benefits should be included.…”
Section: Discussionmentioning
confidence: 99%
“…The U.K. NICE in 2014 updated its guidance for the evaluation of public health interventions recommending both a public sector and a societal approach that means that all relevant costs and benefits should be included. However, in a recent review of interventions for alcohol prevention, for example, it was reported that the methodological challenge of including multisectorial costs and effects is still prevalent and not yet resolved due to difficulties of consistently and accurately measuring nonhealth cost (Hill et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…NICE suggested that school-based interventions should aim to increase knowledge about alcohol, to explore perceptions about alcohol use and to help develop decision-making skills, self-efficacy and self-esteem. The guideline also highlighted the paucity of evidence from economic evaluations of school-based programmes, although a few additional studies have subsequently emerged (see Hill et al 18 for a recent review).…”
Section: Introductionmentioning
confidence: 99%